Sarcoma of the female genitalia. - Koehler, Guenter (Gynecologist) (De Gruyter, 2016)
The subject matter of volume 2 of the 2-volumes-handbook focusses especially on rare sarcomas of the whole female genitalia. These entities include angiosarcoma, the different lipo- and rhabdomyosarcoma as well as newer entities like the PEComa. Furthermore, mixed mullerian tumors like the benign adenofibroma and the malignant adenosarcoma and carcinosarcoma are described in detail. The book provides a description at length of the epidemiology, etiology, pathological anatomy, prognosis, diagnosis, differential diagnosis, imaging and comprehensive therapy of each primary, relapsed and metastasized tumor including surgery, chemo-, hormone-, radio- and targeted therapy. An own chapter is devoted to the problems of fertility and pregnancy in connection with all sarcomas, variants of leiomyoma, atypical smooth muscle tumors, disseminated peritoneal leiomyomatosis, benign metastasizing leiomyoma, intravenous leiomyomatosis and endometrial stromal tumors - endometrial stromal nodules, endometrial stromal tumor with sex cord-like elements (ESTSCLE), uterine tumor resembling ovarian sex-cord tumor (UTROSCT) -and all mixed tumors - of the female genitalia. The book aims to identify and provide diagnostic and therapeutic guidance. The listed tumor entities also constitute a particular diagnostic challenge for pathologists that contains numerous pitfalls and difficulties. This book, therefore, addresses gynecologists and pathologists in both clinical and private practice, but also surgeons and hemato-oncologists.